A proof of principle study of atomoxetine for the prevention of vasovagal syncope: the Prevention of Syncope Trial VI. Issue 11 (20th September 2019) - Sheldon, Robert S; Lei, Lucy; Guzman, Juan C; Kus, Teresa; Ayala-Paredes, Felix A; Angihan, Jesse; Safdar, Shahana; Maxey, Connor; Bennett, Graham; Raj, Satish R
Abstract: Aims: There are few effective therapies for vasovagal syncope (VVS). Pharmacological norepinephrine transporter (NET) inhibition increases sympathetic tone and decreases tilt-induced syncope in healthy subjects. Atomoxetine is a potent and highly selective NET inhibitor. We tested the hypothesis that atomoxetine prevents tilt-induced syncope. Methods and results: Vasovagal syncope patients were given two doses of study drug [randomized to atomoxetine 40 mg ( n = 27) or matched placebo ( n = 29)] 12 h apart, followed by a 60-min drug-free head-up tilt table test. Beat-to-beat heart rate (HR), blood pressure (BP), and cardiac haemodynamics were recorded using non-invasive techniques and stroke volume modelling. Patients were 35 ± 14 years (73% female) with medians of 12 lifetime and 3 prior year faints. Fewer subjects fainted with atomoxetine than with placebo [10/29 vs. 19/27; P = 0.003; risk ratio 0.49 (confidence interval 0.28–0.86)], but equal numbers of patients developed presyncope or syncope (23/29 vs. 21/27). Of patients who developed only presyncope, 87% (13/15) had received atomoxetine. Patients with syncope had lower nadir mean arterial pressure than subjects with only presyncope (39 ± 18 vs. 69 ± 18 mmHg, P < 0.0001), and this was due to lower trough HRs in subjects with syncope (67 ± 30 vs. 103 ± 32 b.p.m., P = 0.006) and insignificantly lower cardiac index (2.20 ± 1.36 vs. 2.84 ± 1.05 L/min/m 2, P = 0.075). There were no significant differences in stroke volume index (32 ± 6 vs. 35 ± 5 mL/m 2, P = 0.29) or systemic vascular resistance index (2156 ± 602 vs. 1790 ± 793 dynes*s/cm 5 *m 2, P = 0.72). Conclusion: Norepinephrine transporter inhibition significantly decreased the risk of tilt-induced syncope in VVS subjects, mainly by blunting reflex bradycardia, thereby preventing final falls in cardiac index and BP.